Application in Product Labeling: Benefits, Challenges, Key Components and Technologies: A review - Adewale, David; Okediran, Iliyasu Kayode; Idris, Musibaudeen Olatunde; Oyewo, Abideen Temitayo; Adefajo, Abdulhafiz Ademola (Borobudur Engineering Review, 2025)
The automation of product labeling has emerged as a critical advancement in manufacturing, enhancing efficiency and precision in packaging processes. This paper provides a comprehensive review of the application of automation in product labeling, focusing on the significant benefits and technological advancements that have transformed the labeling process in modern production environments. The study begins with an overview of the production line and explores how automated labeling systems integrate with other automation technologies to enhance efficiency, accuracy, and flexibility. Key components and technologies, such as vision inspection systems, robotics, and smart labels, are examined in detail, highlighting their role in ensuring precise and consistent labeling. The paper also addresses the challenges and considerations involved in implementing and maintaining automated labeling systems, including integration with existing machinery, maintaining accuracy, and regulatory compliance. In conclusion, the review underscores the significant advancements driving the future of labeling automation, emphasizing how innovations in artificial intelligence (AI), the Industrial Internet of Things (IIoT), and sustainable practices are poised to further revolutionize the industry and drive new levels of efficiency and precision.